Robotics-assisted surgery in gynecology: A single-center experience with the Hugo™ RAS system in India - Manjula Anagani; Ravula Sindura Ganga; Snehalatha Paritala (Women's Health)
Background: Robotics-assisted surgery (RAS) offers several advantages over traditional laparoscopic surgery, such as enhanced precision, dexterity, and ergonomics, and allows stable movements with tremor filtering and motion scaling. The new multi-modular Hugo™ RAS system is commercially available in certain countries and is used in urological, gynecological, and general surgical procedures. Objectives: To document the experience with the use of the Hugo™ RAS system in 20 patients who underwent surgery for various gynecological conditions at a hospital in Hyderabad, India. Design: Real-world single-center study. Methods: Twenty patients (45.3 ± 6.5 years) who were admitted to a tertiary care center (September 2022–2023) underwent hysterectomy ( n  = 18), accessory and cavitated uterine mass excision ( n  = 1), and myomectomy ( n  = 1) using the Hugo™ RAS system. The evaluated outcome parameters included docking time, console time, blood loss (intraoperative and postoperative), length of hospital stay, postoperative complications, and postoperative pain perception measured as per visual analog scale (VAS) scores at multiple time points. Results: The mean docking time was 6.3 ± 2.0 min, and the mean console time was 86.9 ± 20.3 min. Blood loss (intraoperative and postoperative drain) was 103.5 ± 62.4 mL, not requiring blood transfusion for any patient. Per hospital norms, each patient had a hospital stay lasting for 2 days. None of the patients experienced immediate postoperative complications. Minor late complications were observed in two patients. Postoperative pain perception decreased with time. VAS scores were 3.2 ± 0.4 (1 h), 2.2 ± 0.4 (6 h), and 1.0 ± 0.0 (12 h), and no pain was perceived 1 week after surgery. Conclusion: Based on initial experience, the Hugo™ RAS system provides favorable results for gynecological patients, with benefits including efficient docking time, short surgery duration, minimal blood loss, short hospital stay, few postoperative complications, and low pain perception. Future studies comparing the Hugo™ RAS system with other robotic surgical platforms in gynecological procedures are essential.